2008
DOI: 10.1093/fampra/cmn015
|View full text |Cite
|
Sign up to set email alerts
|

Simply no time? Barriers to GPs' participation in primary health care research

Abstract: Doctors' negative attitudes, concerns and ambivalent feelings should be addressed in recruitment strategies, especially when the analysis of EPRs or direct patient contact is required. Some doctors do not participate in research out of principle and will be very difficult to convince.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
113
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 26 publications
13
113
1
4
Order By: Relevance
“…All had graduated from TCM colleges in Canton or Hong Kong, had practiced in San Francisco for more than 10 years, and served a range of 50 to 100 clients per week. With 6 of 10 TCM providers being willing to participate, the possible participation rate of 60% in this study is similar to rates of participation by Western health professionals in a postal survey (59%) (18) and electronic health record research (42%) (19), and is much higher than the 1% to 2% rates in typical intervention studies (20). …”
Section: Methodssupporting
confidence: 58%
“…All had graduated from TCM colleges in Canton or Hong Kong, had practiced in San Francisco for more than 10 years, and served a range of 50 to 100 clients per week. With 6 of 10 TCM providers being willing to participate, the possible participation rate of 60% in this study is similar to rates of participation by Western health professionals in a postal survey (59%) (18) and electronic health record research (42%) (19), and is much higher than the 1% to 2% rates in typical intervention studies (20). …”
Section: Methodssupporting
confidence: 58%
“…20 of the 63 non-responders (30%) participated (see Figure 1, second study arm). The response rate was in line with another German study assessing reasons for non-response or non-participation in a follow-up [40]. …”
Section: Resultssupporting
confidence: 76%
“…In summary, reasons to participate beyond work-related and personal factors include personal or professional interest in a topic and the perceived relevance in research in primary care [19,27,40,42]. …”
Section: Resultsmentioning
confidence: 99%
“…One of the most frequently cited barriers to participation, even among centres showing initial interest in participating in the study, was a lack of capacity to dedicate time or resources to external research projects due to their already considerable work commitments. This was particularly evident among primary care centres; many of whom did not have designated support staff that were able to assist with research activities, an assertion consistent with previous research which has identified time and work commitments as a major barrier to participation in primary care research [38]. Primary care workloads are also very much influenced by seasonal variations in illness.…”
Section: Resultssupporting
confidence: 62%